Structural and Functional Neuroimaging of Restricted and Repetitive Behavior in Autism Spectrum Disorder - Traynor, Jenna M.; Hall, Geoffrey B.C. (Journal of Intellectual Disability - Diagnosis and Treatment, 2015)
A prominent symptom of Autism Spectrum Disorder includes restricted and repetitive behaviours. This symptom has been divided into three subtypes: repetitive motor behaviour, insistence on sameness and circumscribed interests. In the past, the neural correlates of these behaviours have been largely understudied. More recently, neuroimaging studies have pointed to a number of neural networks that may underlay these behaviours. However, results from this work have been varied and remain difficult to integrate. The purpose of this review is to summarize recent neuroimaging studies on restricted and repetitive behaviours in autism, and to provide an organized framework that will permit a clearer understanding of the neural correlates of these behaviours. Using a developmental perspective, this review will identify that there are distinct and overlapping neural networks that are associated with repetitive motor behaviour, insistence on sameness and circumscribed interests. In addition, this review will identify a series of executive and affective function tasks that have proven efficacious in the study of repetitive behaviour.